Clinical features of octogenarian patients with tuberculosis at a tertiary hospital in South Korea. Issue 1 (January 2019) - Min, Jinsoo; Mi Shin, Yoon; Lee, Won Jae; Truong, Tung Thanh; Kang, Eun Seok; An, Jin Young; Choe, Kang Hyeon; Man Lee, Ki
Objective: The growth of the older population is a great challenge for tuberculosis (TB) control in South Korea. This study was performed to investigate the clinical characteristics of and treatment outcomes among octogenarian patients with TB. Methods: We retrospectively analyzed the medical records of 109 patients with TB (age of ≥80 years) from January 2014 to March 2017. Clinical, microbiologic, and radiologic findings were obtained. Results: Fifty-five patients (50.5%) were male, the mean age of the patients was 83.8 years, and 75 patients (68.8%) had pulmonary TB. All patients with pulmonary TB underwent either chest X-ray or chest computed tomography examination, and the results showed that only one-third (n = 33, 39.3%) had active lesions suggestive of TB. Twenty-nine patients (26.4%) had an unfavorable outcome (21 died and 8 were lost to follow-up). Only two TB-related deaths occurred, and both were caused by respiratory failure. Among the 15 non-TB-related deaths, the progression of malignancy and sepsis were the most frequent causes of death. Conclusions: A high mortality rate was observed in octogenarian patients with TB, and most of these deaths were non-TB-related. Among all causes of mortality, solid malignancy was a significant risk factor for death.